Americans and World War - 100 Years Later - Berg, Manfred; Jansen, Axel (The journal of the gilded age and progressive era, 2018)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS1537781418000257/resource/name/firstPage-S1537781418000257a.jpg